Electrochemical Behaviors of Eu (III) on the Liquid Binary Al-Ga Alloy Cathode. Issue 15 (1st January 2019) - Yang, Da-Wei; Chang, Ke-Ke; Hu, Xiao-Fei; Liu, Ya-Lan; Yin, Tai-Qi; Jiang, Shi-Lin; Li, Mei; Han, Wei; Chai, Zhi-Fang; Shi, Wei-Qun
Abstract : The objective of this work is to explore the electrochemical and electrodeposition behaviors of Eu (III) cation at the liquid binary Al-Ga alloy cathode. In addition, the co-reduction behaviors of Eu (III), Al (III) and Ga (III) were also systematically studied on a W electrode. The results indicated that Eu (III) can be reduced on the binary Al-Ga alloy cathode, and Eu (III), Al (III) and Ga (III) also can be co-reduced on the W electrode to form Al-Eu/Ga-Eu intermetallic compounds. At the same time, the isothermal section phase diagram of the Al-Ga-Eu ternary system at 773 K was also calculated. In addition, Al-Eu and Ga-Eu alloys were prepared by potentiostatic and galvanostatic electrolyses in the LiCl-KCl-EuCl3  melt. Finally, the electrodeposition products were characterized by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) coupled with Energy Dispersive Spectroscopy (EDS).